Mechanical Properties of Sisal/Cattail Hybrid-Reinforced Polyester Composites - Silas M. Mbeche; Paul M. Wambua; David N. Githinji (Advances in Materials Science and Engineering, 2020)
Due to environmental and energy conservation concerns, a thrust towards low-cost lightweight materials has resulted in renewed interest in the development of sustainable materials that can replace nonbiodegradable and environmentally unfriendly materials in reinforced composites. In this study, mechanical properties of a hybrid composite consisting of polyester resin reinforced with a blend of sisal and cattail fibres were evaluated. The composite was fabricated using a hand lay-up technique at varying hybrid fibre weight fractions (5 to 25 wt%) while maintaining a constant fibre blend ratio of 50/50. Composites were also prepared at a constant fibre weight fraction of 20% while varying the fibre blend ratio between 0 and 100%. Fabricated composites were then characterised in terms of flexural, tensile, compressive, and impact strengths following ASTM and ISO standards. Results showed that, at a constant fibre blend ratio of 50/50, there was increase in the mechanical properties as the fibre weight fraction increased from 5 to 20%. At a constant fibre weight fraction (20%), a positive improvement in flexural, tensile, and compressive properties was registered as the fibre blend ratio varied between 0 and 75% with optimal values at a sisal/cattail ratio of 75/25. The current study suggests that blending sisal and cattail fibres for production of polyester composites yields hybrid composites with enhanced mechanical properties.